Efficiency and scale economies in banking in new EU countries. (7th October 2008) - Matousek, Roman
In this paper, we provide empirical evidence on bank cost-efficiency in transition countries. Our estimates of the cost-efficiency using a distribution-free approach suggests that among the countries analysed, Estonia, Latvia and Slovenia display the highest X-efficiency while the Czech Republic and Poland show the lowest X-efficiency. Reported X-inefficiency is found to be lowest in the segment of foreign banks that were on average more efficient than other banks. The efficiency of small and foreign banks was also higher when compared with large state-owned banks. Results also indicate that economies of scale decrease with bank size.